TATA KELOLA KOLABORATIF (COLLABORATIVE GOVERNANCE) PEMBANGUNAN PARIWISATA BAJO MOLA WAKATOBI - La Tarifu; Faturachman Alputra Sudirman; Irma Tri Annisya Tombora (Indonesian Association for International Relations, 2022)
The development of Bajo Mola tourism aims to encourage the community-based tourism sector in Wakatobi by increasing the capacity of the community to manage tourism businesses and increasing the local economic opinion of the Bajo Mola community. The Bajo Mola tourism development program involves collaboration between the British Council, Bank Mandiri, the Wakatobi District Government and the Mola Village Community to achieve this goal. This study aims to see how the collaborative governance process in Wakatobi tourism development studies on Bajo Mola Tourism. This research uses qualitative research methods. The research results show that the collaborative governance process for tourism development in Bajo Mola Tourism has been going well. Starting with a face-to-face dialogue, building trust until the collaboration process obtains an intermediate outcome, namely increasing the capacity of the community to manage tourism businesses and increasing the income of the people of Bajo Mola Wakatobi Village. Keywords: Collaborative Governance, Tourism Development, Wakatobi